"Watching the bank balance build up then blow away and the rain clouds do the same": A thematic analysis of South Australian farmers' sources of stress during drought. (August 2016) - Fennell, Kate M.; Jarrett, Claire E.; Kettler, Lisa J.; Dollman, James; Turnbull, Deborah A.
Abstract: Background/aims/method: To investigate causes of farmers' stress during drought, 309 drought-affected South Australian farmers and their spouses, mainly from sheep, cattle and/or gain properties, ranging in age from 23 to 85 years (34.6% female) completed a questionnaire. Demographic and work-related details were collected and participants were asked to list their most stressful experiences in the past month and past 12 months. Results: Most (73.1%) of the sources of stress reported were farm-related. A thematic analysis identified drought, financial pressure and uncertainty about the future as dominant stressors. A range of other more specific drought-related (e.g. poor crop yields, unsatisfactory conditions for livestock, overwhelming workloads) and contextual stressors (e.g. rising input costs, family involvement in the farming business, pressure to take part in community work, lack of understanding of farming from 'outsiders' ) were also identified. Dominant stressors were compounded by non-drought-related issues (e.g. machinery breakdowns ) and non-farm related stressors (e.g. illness and death of loved ones ). Conclusion: Improved awareness of stressors may help to reduce farmers' frustration with outsiders' lack of understanding of their way of life, normalise stressors and thereby reduce stigma and empower farmers to seek help. These findings could also inform the development of targeted mental-health prevention and promotion initiatives for farmers in future periods of drought. Highlights: Financial pressure and uncertainty about the future are major stressors during drought. Contextual factors (e.g. input costs and isolation) add to levels of stress. Most stressors farmers identify during drought are farm-related. Outsiders' lack of understanding of the occupation and way of life compounds stress.